Online Learning Mode in The Post-Pandemic: EFL Learners’ Views - Moh. Hasbullah Isnaini; Pratnyawati Nuridi Suwarso; Salsabil Rihadatul Aisy (Universitas Veteran Bangun Nusantara, 2023)
This study aims to investigate the EFL’s perception of implementing Online Learning in the Post-Pandemic and determine whether online learning suits EFL in post-pandemic situations. This research data was gained from 238 eighth-grade EFL students who experienced online learning after the pandemic. This study utilized a cross-sectional survey design, employing a questionnaire as the primary data collection instrument to uncover information on the online implementation based on two aspects, Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). the instrument was adapted from Rahman (2020) which contained 16 statements with 4 Likert scales. The study revealed that the students responded positively on both aspects, PU and PEOU with the total percentage is 65% and 63% respectively. The positive responses postulate that online learning can be and preferably used as the alternative way of English learning in the post-pandemic situation. However, understanding the instruction and materials is challenging for the students to understand since the students responses reported 55% and 75%, respectively, on the difficulty. To provide and create successful learning, future researchers can further research on providing better instructions and understandable materials for the students.